Procedure concorsuali e governo dell'impresa artigiana in Toscana - Passeri, Riccardo (Firenze University Press, 2005)
This book presents the results of the work of a research group from the University of Florence aimed at underscoring the consequences on the government of craft enterprises of the inequality of the criteria for recognition of the preferential debt of the artisan in insolvency proceedings. The study has also sought to contribute to superseding certain economic-financial criteria utilised to discriminate between enterprises that deserve the recognition of the right and other enterprises, partly through the definition of an alternative criterion that has already been subjected to an initial empirical validation.